Pozycja prawna wdowy w prawie cechowym do połowy XVIII wieku w perspektywie archeologii prawnej na przykładzie miasta Prudnika na Górnym Śląsku - Husak, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
There is no doubt that legal norms regulating the status of widows in guild law were universal and far from particular. As a rule, as seen in guild statutes, the rights of widows in the towns and cities of Wielkopolska were similar to those in Prudnik, Upper Silesia. Nevertheless, as the issue is analysed from the perspective of legal archaeology, it becomes possible to verify the application of statutory law in practice or the existence of customary law, and to examine the practice of everyday life of artisan guilds. When it comes to the town of Prudnik and the local artisan guilds, it has to be said that the 1668 guild chest kept in the Prudnik Museum definitely originated in the town and most likely belonged to the local bakers’ build. It was funded not only by members of the corporation, but also by widows, who had limited guild rights, in particular the right to run a business in their own right. As the most important provisions of the 1547 and 1555 statutes of the Prudnik bakers’ guild show, in the light of the 1668 guild chest, it has to be said that the legal status of widows was a significant exception to the exclusive nature of the guild. Moreover, there is no doubt that women could be members of the Prudnik bakers’ corporation.
Keywords: law; widow; guild; legal archaeology; Prudnik; Upper Silesia (Poland; region)